2021
DOI: 10.1021/acs.inorgchem.1c00849
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal-to-Single-Crystal Transformations of Metal–Organic-Framework-Supported, Site-Isolated Trigonal-Planar Cu(I) Complexes with Labile Ligands

Abstract: Transition-metal complexes bearing labile ligands can be difficult to isolate and study in solution because of unwanted dinucleation or ligand substitution reactions. Metal−organic frameworks (MOFs) provide a unique matrix that allows site isolation and stabilization of well-defined transition-metal complexes that may be of importance as moieties for gas adsorption or catalysis. Herein we report the development of an in situ anion metathesis strategy that facilitates the postsynthetic modification of Cu(I) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…33 SCXRD analysis revealed a linear AuCl complex coordinated to a single N-donor site in 1 (Figure 1, Figures S15, S16), and EDX analysis of the crystals (Table S2, Figure S17) confirmed the expected Mn:Au:Cl ratio of 3:1: with NaBr or NaI in dry methanol for 24 and 48 hours, respectively. 29,30 In both cases, EDX analysis of the crystals indicated that quantitative halide exchange had occurred (see Mn:Cu:X 3:1:1 ratios; X= Br, I; Table S3, Figure S20). Single crystal quality for the bromide and iodide exchanged MOFs was excellent, permitting their examination by SCXRD.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 96%
See 4 more Smart Citations
“…33 SCXRD analysis revealed a linear AuCl complex coordinated to a single N-donor site in 1 (Figure 1, Figures S15, S16), and EDX analysis of the crystals (Table S2, Figure S17) confirmed the expected Mn:Au:Cl ratio of 3:1: with NaBr or NaI in dry methanol for 24 and 48 hours, respectively. 29,30 In both cases, EDX analysis of the crystals indicated that quantitative halide exchange had occurred (see Mn:Cu:X 3:1:1 ratios; X= Br, I; Table S3, Figure S20). Single crystal quality for the bromide and iodide exchanged MOFs was excellent, permitting their examination by SCXRD.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 96%
“…2 (linear), 3 (trigonal planar) and 4 (tetrahedral) are known) 34 that can be interconverted under carefully controlled conditions. 30,35 In addition, we recently demonstrated that 1 can support both tetrahedral and trigonal planar geometries for Cu( i ). 30 Thus, we speculated whether a flexible MOF material could be realised by modulating the Cu( i ) coordination geometry, i.e.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations